Genital Tuberculosis as the Cause of Tuboovarian Abscess in an Immunosuppressed Patient - M. Ilmer; F. Bergauer; K. Friese; I. Mylonas (Hindawi Limited, 2009)
Background. Although tuberculosis (TB) is a major health problem worldwide, primary extrapulmonary tuberculosis (EPTB), and in particular female genital tract infection, remains a rare event. Case Report. A 35-year-old human immunodeficiency virus (HIV) seropositive woman of African descent with lower abdominal pain and fever of two days duration underwent surgery due to left adnexal mass suggesting pelvic inflammatory disease. The surgical situs showed a four quadrant peritonitis, consistent with the clinical symptoms of the patient, provoked by a tuboovarian abscess (TOA) on the left side. All routine diagnostic procedures failed to determine the causative organism/pathogen of the infection. Histopathological evaluation identified a necrotic granulomatous salpingitis and specific PCR analysis corroborated Mycobacterium tuberculosis (M. Tb). Consequently, antituberculotic therapy was provided. Conclusion. In the differential diagnosis of pelvic inflammatory disease, internal genital tuberculosis should be considered. Moreover, physicians should consider tuberculous infections early in the work-up of patients when immunosuppressive conditions are present.